The Feasibility of Extern Training on Ultrasound Fetometry - Surapol Srivongpanich (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Objective:To assess the feasibility of a 3-week sonographic training course on estimating gestational age for externs from the Faculty of Medicine, Siriraj Hospital, Mahidol University. Assessment of the gestational age (GA) was obtained from the measurement of bi-parietal diameter (BPD), head circumference (HC), abdominal circumference (AC) and femur length (FL). Materials and methods: A prospective study was conducted at Pranangklao Hospital. Externs were underwent hands-on practice to measure gestational age according to the second trimester score for gestational age measurement. They were then evaluated by one of the consultant. They were subsequently undertook examination every week. These externs were trained during October 2010 to May 2012. They were assigned as seventeen groups of two and two groups of three. With the total of 40 externs. Results:During the training period, the highest differences between the gestational ages estimated between the externs and te consultants was t 27.5% at the beginning and declined to 11.5% after the end of first week. All externs could determine the gestational ages without significant differences from the consultants within two weeks with the differences ofe 3.75 and 5.70 in the second- and third-week, respectively.Conclusion:Extern training on fetal biometry measurements for gestational age estimation within two weeks is feasible and valuable.